A turn-on fluorescent sensor for the detection of melamine based on the anti-quenching ability of Hg2+ to carbon nanodots. Issue 22 (20th May 2016) - Lei, C. H.; Zhao, X. E.; Jiao, S. L.; He, L.; Li, Y.; Zhu, S. Y.; You, J. M.
Abstract : A simple and time-saving method for the determination of melamine is developed based on the anti-quenching ability of Hg 2+ to C-dots. Abstract : We have proposed here a facile, simple, and cost-effective turn-on assay for melamine with carbon nanodots (C-dots) as a fluorescence reader. Melamine is prone to coordinate with Hg 2+ due to the presence of a multi-nitrogen heterocyclic ring. This property is the cause for the anti-quenching ability of Hg 2+ to C-dots through decreasing the interaction between Hg 2+ and C-dots. By this method, a detection limit of 0.3 μM is obtained, which is approximately 65 times lower than that of the US Food and Drug Administration estimated melamine safety limit of 20 μM. In addition, several real samples including raw milk and milk powder are analyzed using the sensing system with satisfactory recoveries. This research may expand the applications of C-dots as the fluorescent probe in food safety.